A sensitive fluorescence biosensor based on metal ion-mediated DNAzyme activity for amplified detection of acetylcholinesterase. Issue 11 (17th May 2022) - Zhao, Xu-Hua; Dai, Xiao-Chun; Zhou, Ya-Nan; Zhang, Han-Xiao; Cui, Xiao-Hua; Zhai, Xiang; Yu, Bao-Feng; Song, Zhi-Ling
Abstract : In this paper, we developed an amplified fluorescence biosensor for acetylcholinesterase (AChE) activity detection by taking advantage of the mercury ion-mediated Mgzyme (Mg 2+ -dependent DNAzyme) activity. Abstract : In this paper, we developed an amplified fluorescence biosensor for acetylcholinesterase (AChE) activity detection by taking advantage of the mercury ion-mediated Mgzyme (Mg 2+ -dependent DNAzyme) activity. The catalytic activity of Mgzyme can be inhibited by the formation of T–Hg 2+ –T base pairs between the Mgzyme and mercury ions. Therefore, the Mgzyme–Hg 2+ complex has no activity on a molecular beacon (MB) substrate, which afforded a very weak fluorescence background for this biosensor. After the addition of acetylcholinesterase (AChE), the substrate acetylthiocholine could be hydrolyzed to thiocholine, which has a stronger binding power with mercury ions than T–Hg 2+ –T base pairs. Therefore, the Mgzyme activity was recovered. The activated Mgzyme could hybridize with the MB substrate and undergo many cleavage cycles, resulting in a significant increase of fluorescence intensity. This biosensor displayed high sensitivity with the detection limit as low as 0.01 mU mL −1 . Moreover, this design did not require complex composition and sequence design; thus it is simple and convenient. This biosensor was also applied for the determination of AChE in human blood and showed satisfactory results.